Mission trends today : historical and theological perspectives - Mattam, Joseph; Kim, Sebastian C. H.; Annual Meeting of FOIM 1996 : Pune, India) (Mumbai : St. Pauls, 1997)
Contains papers of the 5th Annual Meeting of FOIM held at Pune from 16-19 August 1996.
Includes bibliographical references.
Keywords: Missions -- India -- Congresses; Christianity -- India -- Congresses